Peculiar Covid-19 Effects in the Greater Tokyo Area Revealed by Spatiotemporal Variabilities of Tropospheric Gases and Light-Absorbing Aerosols - Cordero-Carrasco, R (Copernicus Publications, 2022)
This study investigated the spatiotemporal variabilities in nitrogen dioxide (NO2), formaldehyde (HCHO), ozone (O3), and light-absorbing aerosols within the Greater Tokyo Area, Japan, which is the most populous metropolitan area in the world. The analysis is based on total tropospheric column, partial tropospheric column (within the boundary layer), and in situ observations retrieved from multiple platforms as well as additional information obtained from reanalysis and box model simulations. This study mainly covers the 2013-2020 period, focusing on 2020 when air quality was influenced by the coronavirus 2019 (COVID-19) pandemic. Although total and partial tropospheric NO2 columns were reduced by an average of about 10¯% in 2020, reductions exceeding 40¯% occurred in some areas during the pandemic state of emergency. Light-absorbing aerosol levels within the boundary layer were also reduced for most of 2020, while smaller fluctuations in HCHO and O3 were observed. The significantly enhanced degree of weekly cycling of NO2, HCHO, and light-absorbing aerosol found in urban areas during 2020 suggests that, in contrast to other countries, mobility in Japan also dropped on weekends. We conclude that, despite the lack of strict mobility restrictions in Japan, widespread adherence to recommendations designed to limit the COVID-19 spread resulted in unique air quality improvements. © Author(s) 2022.